EVALUATION OF THE EFFICACY AND SAFETY OF 0.05% HALOBETASOL PROPIONATE OINTMENT AND 0.05% CLOBETASOL PROPIONATE OINTMENT IN CHRONIC, LOCALIZED PLAQUE PSORIASIS - Dhurat, Rachita; AJ, KANWAR; VISHWANATH, VISHALAKSHI; KHUNGER, NITI; Grandhi, Sudhakar; Mehta, Nimesh; Bhargava, Amit; Ahluwalia, Amanjit; Vaidya, Rujuta (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Psoriasis is a common, chronic, inflammatory, multisystem disease involving the skin and joints. It accounts for 2.3% of the total dermatology outpatients in India. Corticosteroids have an important role in skin diseases because of their anti-inflammatory, immunosuppressive, and anti-proliferative effects on the keratinocytes. Topical corticosteroids are commonly used in the management of psoriasis and other inflammatory skin disorders. Clobetasol 0.05% ointment and halobetasol 0.05% ointment are synthetic class I super-potent topical corticosteroids with anti-inflammatory, anti-pruritic and vasoconstrictive properties commonly prescribed for the treatment of psoriasis. The current study conducted in 202 patients from 6 centers showed a significant reduction in LPSI scores at end of treatment. The physician's global evaluation rating at end of treatment of almost total clearing of lesion (Grade 4) was reported in 19.2% and 32% patients, marked improvement (Grade 3) in 47.5% and 50.5%, moderate improvement (Grade 2) in 30.3% and 17.5% and mild improvement (Grade 1) in 3% and 0% for Clobetasol and Halobetasol groups respectively. The difference between the two groups for physicians' global evaluation was found to be statistically significant (p=0.019). 19.2% and 27.2% patients in Clobetasol and Halobetasol respectively, showed >75% improvement in photographic assessment (p=0.521). There was a significant difference in the cosmetic acceptability (p=0.042) & in the ease of application (p=0.019) between the two groups. No significant difference was found in serum cortisol levels, in both groups (p=0.074). Therefore this study reaffirms that halobetasol has better efficacy and good tolerability profile compared to clobetasol.